The Use of Various Types of Nutrients and Plants Regulatory Substances in Hydroponic Plants - Ismalida Maftuhatus Samihah; Ai Rohaeti; R Susanti; Talitha Widiatningrum (JURNAL BUDIDAYA PERTANIAN, 2022)
The narrowing of agricultural land, especially in urban areas, accompanied by consumer demand for plant products, requires innovation in the cultivation system. Hydroponics can be a solution because it can be applied to narrow land, not determined by conditions and places, and does not use soil. The provision of appropriate nutrients in hydroponic cultivation techniques can optimize plant growth. This research is a literature study on the provision of alternative nutrients and growth regulators in hydroponic plants. These nutrients include organic fertilizers from animals and plants, NPK fertilizers, plant catalysts, CaCl2, nitrogen, fertimix, rice washing water, NPK phoska, KCl, growmore, vinasse, magnesium, azolla, and glycerides. There are also alternative growth regulators (ZPT), namely gibberellins, auxins, and 'Areta' cytokinins (young coconut water, bamboo shoot extract, and bamboo sprout extract). Some of these nutrients and PGRs have a real and positive effect on plants so that they can be used by farmers of hydroponic cultivation. It was concluded that there are many alternative nutrients and PGRs that have been used and played a role in hydroponic cultivation.